Comparación de la eficiencia de extracción de astaxantina a partir de exoesqueletos de camarón (Litopenaeus vannamei) utilizando como solvente etanol y aceites comestibles como alternativa sostenible. - Zambrano Preciado, Karelys Lilibeth (My University, 2025)
The Ecuadorian shrimp industry generates vast volumes of exoskeletons, a byproduct with high potential for obtaining astaxanthin, a valuable carotenoid with potent antioxidant properties. Given concerns about the environmental and health risks associated with conventional extraction methods using organic solvents, the present study evaluated the efficiency of astaxanthin extraction from Litopenaeus vannamei exoskeletons using a traditional solvent, ethanol, and exploring three edible oils (sunflower, palm, and sesame) as sustainable alternatives. A 2² factorial design was implemented to investigate the impact of two temperatures (26 °C and 50 °C) and two liquid-to-solid ratios (5:1 and 15:1) on astaxanthin content, which was quantified by UV-Vis spectrophotometry at 450 nm. The results showed that ethanol offered the highest overall yield (48,80 ± 1,23 µg/g) under conditions of 50 °C and a 5:1 ratio. Among the edible alternatives, sesame oil stood out significantly (39,11 ± 3,01 µg/g), attributed to its high lipid affinity and good oxidative stability for the pigment. In contrast, sunflower (19,86 ± 0.58 µg/g) and palm (18,32 ± 0,69 µg/g) oils exhibited considerably lower yields. Statistical analysis (ANOVA, p < 0,05) confirmed that solvent type and temperature were the most influential factors in extraction yield. Specifically, temperature proved critical for ethanol, while the liquid-to-solid (L/S) ratio was the dominant factor in sunflower and palm oil extracts. For sesame oil, both temperature and L/S ratio were significant factors. The interaction between temperature and L/S was not statistically significant in any case. These findings position sesame oil as a viable and safe alternative for the sustainable extraction of astaxanthin, offering a method free of toxic solvents. This research not only contributes to the valorization of shrimp waste but also boosts the circular economy in the Ecuadorian aquaculture sector, opening new avenues for industrial applications of this valuable carotenoid.
La industria camaronera ecuatoriana genera grandes volúmenes de exoesqueletos, un subproducto con un alto potencial para la obtención de astaxantina, un valioso carotenoide con potentes propiedades antioxidantes. Ante la preocupación por los riesgos ambientales y sanitarios asociados a los métodos de extracción convencionales con solventes orgánicos, el presente estudio evaluó la eficiencia de la extracción de astaxantina del exoesqueleto de Litopenaeus vannamei utilizando un solvente tradicional, el etanol, y explorando tres aceites comestibles (girasol, palma y ajonjolí) como alternativas sostenibles. Se implementó un diseño factorial 2² para investigar el impacto de dos temperaturas (26 °C y 50 °C) y dos proporciones líquido/sólido (5:1 y 15:1) en el contenido de astaxantina, cuantificado mediante espectrofotometría UV-Vis a 450 nm. Los resultados mostraron que el etanol ofreció el mayor rendimiento global (48,80 ± 1,23 µg/g) bajo condiciones de 50 °C y una relación 5:1. Dentro de las alternativas comestibles, el aceite de ajonjolí destacó significativamente (39,11 ± 3,01 µg/g), lo que se atribuye a su alta afinidad lipídica y buena estabilidad oxidativa para el pigmento. Por el contrario, los aceites de girasol (19,86 ± 0,58 µg/g) y palma (18,32 ± 0,69 µg/g) exhibieron rendimientos considerablemente menores. El análisis estadístico (ANOVA, p < 0,05) confirmó que el tipo de solvente y la temperatura fueron los factores más influyentes en el rendimiento de extracción. Específicamente, la temperatura se mostró crítica para el etanol, mientras que la relación líquido-sólido (L/S) fue el factor dominante en los extractos oleosos de girasol y palma. Para el aceite de ajonjolí, ambos, la temperatura y la relación L/S, resultaron ser factores significativos. La interacción entre temperatura y L/S no fue estadísticamente significativa en ningún caso. Estos hallazgos posicionan al aceite de ajonjolí como una alternativa viable y segura para la extracción sostenible de astaxantina, ofreciendo un método libre de solventes tóxicos. Esta investigación no solo contribuye a la valorización de los residuos camaroneros, sino que también impulsa la economía circular en el sector acuícola ecuatoriano, abriendo nuevas vías para aplicaciones industriales de este valioso carotenoide.
Keywords: ASTAXANTINA; EXOESQUELETO DE CAMARON; ACEITES COMESTIBLES; EXTRACCION SOSTENIBLE